2019
DOI: 10.5194/acp-2019-804
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The impact of Secondary Ice Production on Arctic Stratocumulus

Abstract: In-situ measurements of Arctic clouds frequently show that ice crystal number concentrations (ICNCs) are much higher than the available ice-nucleating particles (INPs), suggesting that Secondary Ice Production (SIP) may be active. Here we use a Lagrangian Parcel Model and a Large Eddy Simulation to investigate the impact of three SIP mechanisms (rime-splintering, break-up from ice-ice 20 collisions and droplet-shattering) on a summer Arctic stratocumulus case observed during the Cloud Coupling And Climate Inte… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…Another SIP mechanism, identified in recent laboratory studies (Leisner et al, 2014;75 Lauber et al, 2018), is the generation of ice fragments from shattering of relatively large frozen drops. This process however, while it is very efficient in convective clouds (Korolev et al, 2019), it has been found ineffective in polar regions (Fu et al, 2019;Sotiropoulou et al, 2020). This is in agreement with Lawson et al (2017) and Sullivan et al (2018a) who have shown that drop-shattering occurs in clouds with a relatively warm cloud base.…”
supporting
confidence: 64%
See 3 more Smart Citations
“…Another SIP mechanism, identified in recent laboratory studies (Leisner et al, 2014;75 Lauber et al, 2018), is the generation of ice fragments from shattering of relatively large frozen drops. This process however, while it is very efficient in convective clouds (Korolev et al, 2019), it has been found ineffective in polar regions (Fu et al, 2019;Sotiropoulou et al, 2020). This is in agreement with Lawson et al (2017) and Sullivan et al (2018a) who have shown that drop-shattering occurs in clouds with a relatively warm cloud base.…”
supporting
confidence: 64%
“…(Mossop and Hallett, 1974;Choularton et al, 1980). However, recent studies have shown that H-M cannot sufficiently explain the enhanced ICNCs observed in both Arctic (Sotiropoulou et al, 2020) and Antarctic (Young et 70 al., 2019) clouds. While some Antarctic studies (Vergara-Temprado et al, 2018;Young et al, 2019) suggest that the underestimation of ice multiplication in models might be related to uncertainties in the description of the H-M process, we argue that this is likely driven by the fact that almost no models include other SIP mechanisms.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…be reinforced at temperatures favorable for secondary ice formation (Sotiropoulou et al, 2019), where even higher ice crystal concentrations than simulated in HighINP may further increase precipitation and induce a more rapid stratocumulus breakup (Abel et al, 2017). Nevertheless, open questions remain.…”
Section: Discussionmentioning
confidence: 99%